A pharmacometric approach to optimal use of second line drugs for multidrug-resistant tuberculosis - Court, Richard Gray (Department of Medicine, 2023)
Until the recent introduction of short course regimens, treatment regimens for multidrug resistant TB (MDR-TB) were long and toxic. Consequently, only approximately half of MDRTB patients completed their treatment. TB dosing guidelines have historically been unrefined with little consideration for pharmacokinetic/pharmacodynamic relationships. Large knowledge gaps therefore exist in the understanding of pharmacokinetic/pharmacodynamic relationships for both efficacy and toxicity in MDR-TB. My PhD used clinical pharmacology approaches to improve the understanding of drug exposures, toxicity, and exposure-toxicity relationships during the first 12 weeks of MDR-TB therapy. Aims and methods 1. Using non-compartmental analyses, describe the pharmacokinetics of cycloserine and, using regression modelling, explore the association of covariates with cycloserine exposure. 2. Using validated screening tools, describe the incidence of neuropsychiatric toxicity in MDR-TB patients, and explore associations with cycloserine pharmacokinetics. 3. Using a validated pain-rating scale in a crossover study design, investigate whether the addition of a local anaesthetic reduces kanamycin-related injection pain, and explore effects on kanamycin pharmacokinetics. 4. Using geometric mean ratios, compare the exposures of crushed versus whole formulations of pyrazinamide, moxifloxacin, ethionamide, ethambutol, cycloserine, and isoniazid. Results and conclusions We found no measurable terizidone in plasma supporting the hypothesis that terizidone is hydrolysed pre-systemically to cycloserine. The cycloserine time-concentration profile supports once daily dosing of terizidone. We describe a high incidence of peripheral neuropathy in MDR-TB patients with both cycloserine clearance and high-dose pyridoxine significantly associated with neuropathy on multivariate analysis. The addition of a local anaesthetic reduced the pain experienced by MDR-TB patients in the first 15 minutes post intramuscular administration of kanamycin, which could improve adherence to MDR-TB treatment. We also found the bioavailability of crushed isoniazid to be approximately 42% less than the whole tablet formulation, and therefore recommend that the crushing of isoniazid be avoided. Although some recent treatment advances have improved MDR-TB outcomes, enhancing the understanding of drugs used to treat MDR-TB, which continues to have an unacceptably high mortality and treatment-related morbidity, is a public health priority. This thesis comprises four peer-reviewed publications, all of which made a pragmatic contribution to the fight against MDR-TB.